Comparative analysis of lipid‐mediated CRISPR‐Cas9 genome editing techniques. (14th March 2018) - Ringer, Kelsey P.; Roth, Mark G.; Garey, Mitchell S.; Piorczynski, Ted B.; Suli, Arminda; Hansen, Jason M.; Alder, Jonathan K.
Abstract: CRISPR‐Cas technology has revolutionized genome engineering. While Cas9 was not the first programmable endonuclease identified, its simplicity of use has driven widespread adoption in a short period of time. While CRISPR‐Cas genome editing holds enormous potential for clinical applications, its use in laboratory settings for genotype‐phenotype studies and genome‐wide screens has led to breakthroughs in the understanding of many molecular pathways. Numerous protocols have been described for introducing CRISPR‐Cas components into cells, and here we sought to simplify and optimize a protocol for genome editing using readily available and inexpensive tools. We compared plasmid, ribonucleoprotein (RNP), and RNA transfection to determine which was method was most optimal for editing cells in a laboratory setting. We limited our comparison to lipofection‐mediated introduction because the reagents are widely available. To facilitate optimization, we developed a novel reporter assay to measure gene disruption and the introduction of a variety of exogenous DNA tags. Each method efficiently disrupted endogenous genes and was able to stimulate the introduction of foreign DNA at specific sites, albeit to varying efficiencies. RNP transfection produced the highest level of gene disruption and was the most rapid and efficient method overall. Finally, we show that very short homology arms of 30 base pairs can mediate site‐specific editing. The methods described here should broaden the accessibility of RNP‐mediated lipofection for laboratory genome‐editing experiments.